Synthesis of precisely functionalizable curved nanographenes via graphitization-induced regioselective chlorination in a mechanochemical Scholl Reaction - Stanojkovic, Jovana (2023)
While the synthesis of nanographenes has advanced greatly in the past few years, development of their atomically precise functionalization strategies remains rare. The ability to modify the carbon scaffold translates to controlling, adjusting, and adapting molecular properties. Towards this end, here, we show that mechanochemistry is capable of transforming graphitization precursors directly into chlorinated curved nanographenes through a Scholl reaction. The halogenation occurs in a regioselective, high-yielding, and general manner. Density Functional Theory (DFT) calculations suggest that graphitization activates specific edge-positions for chlorination. The chlorine atoms allow for precise chemical modification of the nanographenes through a Suzuki or a nucleophilic aromatic substitution reaction. The edge modification enables modulation of material properties. Among the molecules prepared, corannulene-coronene hybrids and laterally fully π-extended helicenes, heptabenzo[5]superhelicenes, are particularly noteworthy.